FGF21 Signals to Glutamatergic Neurons in the Ventromedial Hypothalamus to Suppress Carbohydrate Intake - Jensen-Cody, Sharon O; Flippo, Kyle H; Claflin, Kristin E; Yavuz, Yavuz; Sapouckey, Sarah A; Walters, Grant C; Usachev, Yuriy M; Atasoy, Deniz; Gillum, Matthew P; Potthoff, Matthew J (Cell metabolism, 2020)
Fibroblast growth factor 21 (FGF21) is an endocrine hormone produced by the liver that regulates nutrient and metabolic homeostasis. FGF21 production is increased in response to macronutrient imbalance and signals to the brain to suppress sugar intake and sweet-taste preference. However, the central targets mediating these effects have been unclear. Here, we identify FGF21 target cells in the hypothalamus and reveal that FGF21 signaling to glutamatergic neurons is both necessary and sufficient to mediate FGF21-induced sugar suppression and sweet-taste preference. Moreover, we show that FGF21 acts directly in the ventromedial hypothalamus (VMH) to specifically regulate sucrose intake, but not non-nutritive sweet-taste preference, body weight, or energy expenditure. Finally, our data demonstrate that FGF21 affects neuronal activity by increasing activation and excitability of neurons in the VMH. Thus, FGF21 signaling to glutamatergic neurons in the VMH is an important component of the neurocircuitry that functions to regulate sucrose intake.